INVESTIGATING THE EFFECT OF COVID-19 ON HUMAN RESOURCE MANAGEMENT AND NON-FINANCIAL JOB SATISFACTION: EMPIRICAL EVIDENCE FROM THE RMG SECTOR OF BANGLADESH - Sharif, Md. Azmir; Rahman, Md. Atiqur; Mallik, Mita Rani (Bangladesh Journal of Multidisciplinary Scientific Research, 2022)
This study aims to assess the impact on Human Resource Management (HRM) practices of the Ready-made Garments Sector, evaluate major changes due to COVID-19 in HRM, and examine employees’ non-financial job satisfaction during COVID-19. This study collected data from 100 randomly selected respondents from Ready-made Garments of Bangladesh to accomplish these objectives. The findings show that job satisfaction (non-financial) has positive significant (p<0.05) relation with working environment conditions (WEC) and also has a positive significant (p<0.05) association with employee management relationship (EMR). In contrast, a similar positive correlation is also found between WEC and EMR. However, during COVID-19, non-financial job satisfaction, including hand sanitizer, soap, masks, sick leave, health safety issues, etc., was increased and indicated a satisfactory rank. This suggests that most firms maintain health issues, safety, and others during a pandemic, which enhances non-financial job satisfaction. On the contrary, financial benefits are reduced, loss of jobs, and lack of job safety increases, which cannot be ignored. Moreover, this study also recommends several policies that may improve the employees’ productivity and the industry as a whole. JEL Classification Codes: G32, F65, L66, L25, M41.